2002
DOI: 10.1136/pmj.78.916.76
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemesis gravidarum: current concepts and management

Abstract: Hyperemesis gravidarum is a common problem for an obstetrician. Though nausea and vomiting are quite common in pregnancy, hyperemesis is found in only 1–20 patients per 1000. In this practical review, a general outline of the syndrome, its relation to the gastrointestinal system and thyroid, mild and rare severe complications, and conventional treatment versus newer options are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 54 publications
0
47
0
1
Order By: Relevance
“…Immunological, hormonal, and psychological factors associated with pregnancy may play an etiologic role and risk factors include hyperthyroidism, psychiatric illness, molar pregnancy, preexisting diabetes, and multiple pregnancies. 2,3 The diagnosis is clinical-intractable, dehydrating vomiting, typically between 4 and 10 weeks' gestation. Liver dysfunction occurs in 50% patients with aminotransferases up to 20-fold elevation and with occasional jaundice.…”
mentioning
confidence: 99%
“…Immunological, hormonal, and psychological factors associated with pregnancy may play an etiologic role and risk factors include hyperthyroidism, psychiatric illness, molar pregnancy, preexisting diabetes, and multiple pregnancies. 2,3 The diagnosis is clinical-intractable, dehydrating vomiting, typically between 4 and 10 weeks' gestation. Liver dysfunction occurs in 50% patients with aminotransferases up to 20-fold elevation and with occasional jaundice.…”
mentioning
confidence: 99%
“…Figure 1, illustrates how psychological stress may exacerbate NVP and steroids are involved but the use of hydrocortisone and methylprednisolone on successful cessation of HG is not clear. 8,29 The antiemetic properties of corticosteroid are possibly due to various factors acting in concert or individually and prostaglandin antagonism, 47 stimulation of endorphins that elevate mood and appetite stimulation and reduction in tryptophan in neural tissue have been suggested. 48,49 It can be postulated that in pregnancy, disturbances in metabolic control and increased requirements for glucose give rise to mild hypoglycaemia and during these situations, such as following overnight fasting; hypoglycaemia may trigger nausea and vomiting.…”
Section: Metabolic Control In Pregnancymentioning
confidence: 99%
“…6,22,40 Kuscu and Koyuncu, suggested that NVP beyond the second trimester are indicative of H. Pylori infection and other studies reported that the severity of NVP experienced correlated with the density of H. Pylori. 29,40 Maternal diet, during pre-conception and in pregnancy is associated with the incidence and severity of NVP. Adequate sea-food, vegetables and water intake in prepregnancy reduce development of HG and it has been observed that women with NVP had diet high in calories, carbohydrates and added dietary sugars that came mostly from soft drinks but the study could not determine if consumption of such diet was to mitigate symptoms of NVP.…”
Section: External Factorsmentioning
confidence: 99%
See 2 more Smart Citations